Transcriptional patterns of Coffea arabica L. nitrate reductase, glutamine and asparagine synthetase genes are modulated under nitrogen suppression and coffee leaf rust - Baba, Viviane Yumi; Braghini, Masako Toma; Dos Santos, Tiago Benedito; De Carvalho, Kenia; Soares, João Danillo Moura; Ivamoto-Suzuki, Suzana Tiemi [UNESP]; Maluf, Mirian P.; Padilha, Lilian; Paccola-Meirelles, Luzia D.; Pereira, Luiz Filipe; Domingues, Douglas S. [UNESP] (PeerJ, 2020)
This study evaluated the transcriptional profile of genes related to nitrogen (N) assimilation in coffee plants susceptible and resistant to rust fungi under N sufficiency and N suppression. For this purpose, we inoculated young coffee leaves with Hemileia vastatrix uredospores and collected them at 0, 12, 24 and 48 hours post-inoculation (HPI) to evaluate the relative expressions of genes encoding cytosolic glutamine synthetase (CaGS1), plastid glutamine synthetase (CaGS2), nitrate reductase (CaNR), and asparagine synthetase (CaAS). The genes exhibited distinct patterns of transcriptional modulation for the different genotypes and N nutritional regimes. The resistant genotype (I59) presented high levels of transcription in response to pathogen inoculation for CaNR and CaGS1 genes, evaluated under N sufficiency in the initial moments of infection (12 HPI). The gene CaGS1 also showed a peak at 48 HPI. The susceptible genotype (CV99) showed increased transcript rates of CaNR at 12 and 24 HPI in response to rust inoculation. The transcriptional patterns observed for CV99, under N suppression, were high levels for CaAS and CaGS2 at all post-inoculation times in response to coffee leaf rust disease. In addition, CaGS1 was up-regulated at 48 HPI for CV99. Cultivar I59 showed high transcript levels at 12 HPI for CaAS and peaks at 24 and 48 HPI for CaGS2 in inoculated samples. Consequently, total chlorophyl concentration was influenced by N suppression and by rust infection. Regarding enzyme activities in vitro for glutamine synthetase and CaNR, there was an increase in infected coffee leaves (I59) and under N sufficiency. Moreover, CV99 was modulated in both N nutritional regimes for GS activity in response to rust. Our results indicate that N transport genes trigger a differential modulation between genotypes through the action of rust disease.
Keywords: Gene expression; Genotypic response; Hemileia vastatrix; Mineral nutrition; N assimilation; RT-qPCR